Comparison Sequences of Pick and Place System Controlled Using PLC - Khaleel, Shahad Sarmad; Salloom, Maher Yahya; Mohammed, Ahmed Zidan (Al-Nahrain Journal for Engineering Sciences, 2020)
Pick and place system is one of the significant employments of modern robots utilized in industrial environments. The objective of this research is to make a comparison of time sequences by combining multiple axes of sequences. A pick-place system implemented with pneumatic linear double-acting cylinders to applicator in automated systems processes for manufacturing. The challenge of 3-axes movement control was achieved using the PLC (Programmable Logic Controller) controller such that the merging between two or three axes was achieved according to the selected sequence of the program. The outcomes show the contrasted sequences and the reference in a constant velocity. The main variable parameter is the number of steps for each sequence. The combination of two axes has developed the sequence and reduced in number of sequences for a path. At last, one of the important factors in moving products industry is the smooth product’s movement, because any high speed might cause a vibration in the system and lead to a decreased positioning accuracy.